CORE-VTRCC Cruise Report: Geophysical Acquisition and Seafloor Sampling along the Vitória-Trindade Ridge - Gabriel Tagliaro; Mateus A. C. Gama; Adolfo N. Britzke; Vinicius H. A. Louro; Pedro Bauli; Gabriela C. Patines; Gabrielle D. Bonifatto; Ana C. B. Vieira; Beatriz B. S. Silva; Geandré C. Boni; Luan K. Pantoja; Paula P. Sergipe; et al. (Scientific Data, 2024)
Abstract This work reports the data obtained by the multidisciplinary cruise CORE-VTRCC surveying on the region around the Vitória-Trindade Ridge (VTR) aboard the vessel NHo Cruzeiro do Sul (October 18th to November 6th, 2021). The main objectives of the VTRCC Cruise were (1) to assess the role of the VTR as an oceanographic barrier for bottom currents along the Brazilian margin; and (2) to characterize the morphology of the volcanic seamounts and its relationships with the carbonate sediments that cover it. For that, we performed multibeam bathymetry, magnetometry, high-resolution multichannel seismic survey, subbottom profiling survey, and seafloor sampling along the VTR and along the Columbia Deepwater Channel. The raw dataset was processed for quality control and organized for public access. When required, additional geophysical processing occurred to improve data quality. Seafloor samples are characterized based on the concentration of its biofacies, the sediment grain-sizes and the morphology of rhodoliths sampled. The dataset reveals comprehensively the geological and oceanographic heterogeneity of the region around the VTR.